Case Report: The double-edged sword: cytokine release syndrome and rapid tumor response in a patient treated with amivantamab and chemotherapy - Cui, Pengfei; Sun, Guannan; Zhou, Gang; Guo, Xueguang; Huang, Haili; Yang, Jing; Li, Na; Tan, Jing; Hu, Yi; Zhang, Dong (Frontiers in Oncology, 2026)
ObjectiveTo report a well-documented case of cytokine release syndrome (CRS) following the first cycle of amivantamab combined with chemotherapy in a patient with osimertinib-resistant EGFR-mutant non-small cell lung cancer (NSCLC), highlighting its diagnosis, management, and association with a rapid antitumor response.Case summaryA 72-year-old man with metastatic lung adenocarcinoma (epidermal growth factor receptor (EGFR) exon 19 del) progressing on osimertinib initiated treatment with amivantamab, pemetrexed, and carboplatin. Five days post-infusion, he developed a persistent fever unresponsive to broad-spectrum antibiotics. Infection was rigorously excluded based on normal procalcitonin, undetectable endotoxin, and negative cultures. In contrast, inflammatory markers were elevated (peak CRP (C−reactive protein) 16.6 mg/dL), and cytokine profiling revealed significant elevations in IL−6 (interleukin−6) (107 pg/mL), sIL-2R (soluble interleukin−2 receptor), TNF-α (tumor necrosis factor−alpha), and IL-10, accompanied by profound lymphopenia. A computed tomography (CT) scan demonstrated a significant tumor reduction. A diagnosis of grade 1 CRS (by ASTCT (American Society for Transplantation and Cellular Therapy) criteria) was made. The fever and inflammatory markers resolved with supportive care.FindingsThis case provides comprehensive clinical and serological evidence of amivantamab-chemotherapy-induced CRS. The temporal association between the robust cytokine surge, characteristic of T-cell activation, and the observed rapid tumor regression suggests that the same immunologic mechanism likely underpinned both the efficacy and the toxicity.ConclusionCRS is an important adverse event associated with amivantamab-based combination therapy in solid tumors. Early recognition, based on clinical suspicion and characteristic cytokine profiles, and differentiation from infection are crucial. The concurrent rapid tumor response indicates that effective immune activation drives both toxicity and efficacy, underscoring the need for optimal management strategies to mitigate CRS without compromising antitumor activity.